"Applications of Nanotechnology in Concrete Design: Proceedings of the International Conference Held at the University of Dundee, Scotland, UK on 7 Jul" - Dhir (Ravindra K); Newlands (Moray D); Csetenyi (Laszlo J) (2005)
Design of Concrete Structures
40
Keywords: Design of Concrete Structures